Pengaruh Penggunaan Aplikasi Video Pembelajaran Menggunakan Camtasia terhadap Hasil Belajar Siswa pada Materi Sistem Reproduksi di SMAN 1 Teluk Mengkudu - Rabiyatul Adawiyah (Bioedunis Journal, 2022)
This study aims to determine the increase in learning outcomes by using computer-based learning videos on reproductive system material. The type of research that has been done is class action research. The subjects in this study were class XI IPA 1, which consisted of 41 people. The data collection tool used is multiple choice tests. The results showed that the average value of the learning outcomes of the first cycle was 59.02 with 58.5% classical completeness while the average value of the second cycle learning outcomes was 71.59 with 80.5% classical completeness. The results of observations on student activity showed an increase from cycle I with a percentage value of 52.38% including the less active category, while student activity in cycle II was 82.47 including the active category. From the data that has been obtained shows that computer-based learning using Camtasia can improve student learning outcomes on the subject matter of the human reproductive system